The Impact of obesity and diabetes mellitus on pancreatic cancer: Molecular mechanisms and clinical perspectives - Quoc Lam, B.; Shrivastava, S.K.; Shrivastava, A.; Shankar, S.; Srivastava, R.K. (Blackwell Publishing Inc., 2020)
The incidence of obesity and type 2 diabetes (T2DM) in the Western world has increased dramatically during the recent decades. According to the American Cancer Society, pancreatic cancer (PC) is the fourth leading cause of cancer-related death in the United States. The relationship among obesity, T2DM and PC is complex. Due to increase in obesity, diabetes, alcohol consumption and sedentary lifestyle, the mortality due to PC is expected to rise significantly by year 2040. The underlying mechanisms by which diabetes and obesity contribute to pancreatic tumorigenesis are not well understood. Furthermore, metabolism and microenvironment within the pancreas can also modulate pancreatic carcinogenesis. The risk of PC on a population level may be reduced by modifiable lifestyle risk factors. In this review, the interactions of diabetes and obesity to PC development were summarized, and novel strategies for the prevention and treatment of diabetes and PC were discussed. © 2020 The Authors. Journal of Cellular and Molecular Medicine published by John Wiley & Sons Ltd and Foundation for Cellular and Molecular Medicine.
Keywords: alcoholism; diabetes mellitus; obesity; pancreatic cancers; prevention